Penerapan Digital Leadership dan Profil Kinerja Keuangan pada Perusahaan Startup di Indonesia - Sherina Santoso; Vania Sugiharto; Juniarti Juniarti (Business Accounting Review, 2021)
This study aims to explore the application of digital leadership and its impact on the financialperformance of startup companies in Indonesia. In this study, an online questionnaire-based surveywas conducted to collect data from startup companies in Indonesia. The sample in this study is amedium-sized startup company and has an application or website that customers can use, and thefinal sample results are 37 companies. This study uses cross-sectional data and will be analyzedusing WarpPLS 7.0 software. This study found that digital leadership has a positive and significanteffect on financial and non-financial performance. However, the best model in this study is the directinfluence of digital leadership on financial performance.